The death trade [large type] - Higgins, Jack, 1929- (Thorndike Press large print core series., 2014)
An eminent Iranian scientist has made a startling breakthrough in nuclear weapons research, but he can't stand the thought of his regime owning the bomb. He would run if he could, but if he does, his family dies. He is desperate; he doesn't know what to do. It is up to Sean Dillon and the rest of the small band known as the Prime Minister's private army to think of a plan. Most particularly, it is up to their newest member, an intelligence captain and Afghan war hero named Sara Gideon, who thinks there just might be a way to pull it off.